THE LEGALITY OF DESTROYING ILLEGAL IMPORTED GROCERIES : A STUDY OF ISLAMIC ECONOMIC LAW’S PERSPECTIVE - Hasan, Badri; Annisa, Thaharah; Fauzan, Faisal (JURISTA: Jurnal Hukum dan Keadilan, 2024)
Abstract This article aims to examine the perspective of Islamic economic law on the destruction of illegally imported foodstuffs. This research uses an empirical juridical approach, where the main data is obtained from interviews and observations in the field, as well as studies of legal doctrine, and analyses of statutory norms.  In addition, the author also uses secondary data sourced from various sources related to this research. The results of the study show that: first, the practice of destroying illegally imported groceries is carried out on groceries that have met the criteria for destruction, including groceries in rotten, expired, and unfit for use conditions. Second, the legal basis for destruction is Minister of Finance Regulation Number 240/PMK.06/2012 concerning Procedures for the Management of State Property Originating from Ex-Customs and Excise Assets. Third, in terms of Islamic law, the destruction of illegal imported groceries at Banda Aceh Customs is in accordance with sharia economic law.